PEMANFAATAN LIMBAH LIGNOSELLULOSA UNTUK GAS BAKAR DENGAN METODE FERMENTASI - Tjutju Nurhayati Syahri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The gasification of lignocellulosic waste was conducted by fermentation method at thermophilic condition (45 -55°C). The material was obtained from vegetable market at Bogor. The gasification trial made in pilot scale reactor of having capacity of 30 m3 and equipped with gas holder of 50 m3, steam boiler of 50 kg/h and dual generator of 17.5 kVA. The waste was cut first become 1-3 cm long on choper of 0.3 m3/h volume. Parameter of fermentation choosed on 10 m3 volume actif and retention time was 20.9 daysThe result revealed that thermophilic fermentation of waste which had total solid about 22.3 % and ash about 33.9 % and feeding about 478 kg fresh waste per day produced biogas about 28.7 m3 per day on methane content about 54.5 %, productivity about 2.9 m3 per m3 reactor per day and efficiency of conversion about 57 %.The total of fuel consumption along fermentation per day was 4.34 hours of man hours work about 1.16 MJ and it was from 1 tube LPG of 12.5 kg and 14.31 diesel. LPG was used for steam boiler can be changed with 31.2 m3 biogas per day. In this case the production of biogas per day cannot be dropped for the total of fuel consumption even steam boiler. The fermentation of 22965 kg wet lignocellulosic waste produced gas bio about 1380 m3 and wet residu for compos raw material about 16430 kg. The biogas production was equavalent with 44 LPG container of 12.5 kg.